GAYA KONSUMSI DAN PERILAKU KONSUMEN GENERASI Z DI FOOD COURD AL MADINAH SURABAYA - Eva; Aminatuz Zuhroh; Abel Maulid Kurniawan; Moh. Ilham (Media Inovasi Pendidikan dan Publikasi, 2024)
This research aims to investigate the consumption styles and consumer behavior of Generation Z at the Al Madinah Surabaya Food Court. Generation Z, which is a group of consumers born in the mid-1990s to early 2010s, has unique consumption characteristics and preferences that can influence food choices and shopping decisions in food court environments. This study uses a qualitative approach with in-depth interviews and participant observation as data collection methods. This research was conducted in Surabaya in the first to third week of October. Qualitative methods were used with 6 respondents in in-depth interviews (virtual and live based). The research results show that the lifestyle and behavior phenomenon of Gen Z consumers at the Al-Madinah food court develops from culture, needs and price factors. Gen Z as customers at the food court experience emotional satisfaction. Gen Z's activities, behavior and lifestyle are channeled through the AIO (Activity, Interest, Opinion) lifestyle dimensions in the food court. The suggestion for the Al-Madinah food court is that it must innovate so that it has unique characteristics. Innovation can be expressed in the decoration of the place and also dare to release new menu variants that are interesting, unique but also worth having. This effort focuses on providing emotional satisfaction to Gen Z. Following trends is also very necessary considering that Gen Z has the characteristic of liking challenges and going viral.